2016
DOI: 10.1097/acm.0000000000001131
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Continuing Medical Education: Clinical Coaching as a Tool for Ongoing Professional Development

Abstract: To better understand the impact and generalizability of clinical coaching, a larger, longitudinal study is required to look at patient and provider outcomes in detail. Further refinement of the SCA role to meet faculty needs is needed and could include faculty development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…We found that both coaches and funded educators experienced enhanced global job satisfaction. Coaches are known to enjoy role satisfaction, but the finding of the impact of coaching on global satisfaction is novel [ 10 ]. Self-efficacy fosters job satisfaction, and participants identified sources of reward that enhanced their self-efficacy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that both coaches and funded educators experienced enhanced global job satisfaction. Coaches are known to enjoy role satisfaction, but the finding of the impact of coaching on global satisfaction is novel [ 10 ]. Self-efficacy fosters job satisfaction, and participants identified sources of reward that enhanced their self-efficacy [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 8 ] The coach promotes learners’ self-improvement through feedback, self-reflection, and goal setting [ 8 , 9 ]. Learners working with coaches endorse enhanced comfort with clinical practice, greater self-awareness, and increased receipt of feedback [ 10 13 ]. Likewise, coaches experience benefits including professional development, community building, and role satisfaction [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more hands-on approach was used at Massachusetts General Hospital (MGH), with senior clinical advisors acting as clinical coaches to early-career hospitalists. 38 Clinical coaching is a voluntary relationship between colleagues which focuses on a participant's strength and uses self-evaluation and feedback to improve clinical performance. 39 The program at MGH entailed twelve volunteer senior clinical advisors with more than 5 years of post-residency experience to coach 25 early-career hospitalists on medical decision-making, data interpretation, and clinical exam findings.…”
Section: Peer Feedback In Hospital Medicinementioning
confidence: 99%
“…It is commonly employed in sports coaching and is strongly supported as essential to coach development 83. Iyasere et al84 notes that the practice of medicine is built on the apprenticeship model. Cognitive apprenticeship has been used to teach coaching in business and leadership programs 85.…”
Section: Faculty Development For the Coaching Rolementioning
confidence: 99%